DAMPAK PENERAPAN MODEL PEMBELAJARAN CTL TERINTEGRASI MEDIA 3D APLIKASI ASSEMBLR EDU PADA HASIL BELAJAR KOGNITIF PENDIDIKAN PANCASILA PESERTA DIDIK KELAS V SEKOLAH DASAR - Nesa Lia, Eva; Muhisom; Agung Dian Putra; Ulwan Syafrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problems are the low cognitive learning outcomes which are mostly belowthe Level of Achievement Completion Criteria standard for fifth grade students atSD Negeri 1 Kaliawi. This study aims to examine the impact of implementing theCTL model integrated with 3D media from the assemblr edu application on thecognitive learning outcomes of fifth grade students in Pancasila Education. Thisstudy uses a quasi experimental method with a nonequivalent control group design.The study population consists of students from classes VA and VB, totalling 44students, and the sample was determined using purposive sampling technique. Thestudy approach is quantitative with data collection through multiple choice tests. Theresults of data analysis using simple linear regression and supported by anindependent sample t-test showed a significance value of 0.000 < 0.05 and 0,049 <0,05 indicating that there is an impact of CTL model integrated with 3D media fromthe assemblr edu application on the cognitive learning outcomes of fifth gradestudents in Pancasila Education at SD Negeri 1 Kaliawi.